Correction: Magazine et al. Mutations and Evolution of the SARS-CoV-2 Spike Protein. Viruses 2022, 14, 640 - Nicholas Magazine; Tianyi Zhang; Yingying Wu; Michael C. McGee; Gianluca Veggiani; Weishan Huang (Viruses, 2023)
In the original publication [...]